SAIL SPORT AS A SCHOOL PHYSICAL EDUCATION PRACTICAL (Fiep Bulletin - online, 2014)
ABSTRACT  During the history of the humanity Educational and the Physical Education come suffering a great process from development, stimulated for diverse reasons. Some debates and research had been, e still is being elaborated for some studious and personalities of diverse segments of the society, with this, the function of the Professor if finds in constant perfectioning. In the pertaining to school environment in many aspects it did not follow the occurred changes in the education forms. It disciplines it Pertaining to school Physical Education until certain point advanced, however, many times imprisoned in the administrative bureaucracy and the lack of physical structure, it still lacks of definitive actions to follow a globalized world, that it demands each time plus a bigger dynamics and a bigger gamma of new challenges, to continue offering to the pupils a captivate and efficient education. The sports used traditionally in the education institutions are historically efficient tools, however already practical its does not withhold the unanimous preference of the pupils how much.On the basis of this thought, the present work developed a philosophical research that comes to answer the central problem, after to have established the hypotheses, examined and analyzed the existing facts and synthesized the evidence inside of a viable theoretical model. This analysis is finished then identifying the solution of the question: the sport the sail withholds conditions to develop a methodology of Physical Education, equivalent with the ones of the traditional pertaining to school sports and inside of the determination and objectives of the educational agencies maintain of this disciplines pertaining to school?
Keywords: Teaching methodology; sport the candle; educational sport; School Physical Education; National Curricular Parameters